2010
DOI: 10.1007/s10482-010-9489-2
|View full text |Cite
|
Sign up to set email alerts
|

Rhodotorula taiwanensis sp. nov., a novel yeast species from a plant in Taiwan

Abstract: A novel anamorphic yeast strain, A1-01(T), belonging to the genus Rhodotorula was isolated from a plant in Taiwan and analysed morphologically, physiologically and phylogenetically. Neither ballistoconidia nor sexual reproduction was observed. Sequence analysis of the 26S rRNA gene and the ITS region indicate that Rhodosporidium sphaerocarpum is the most closely related species, with 14 and 24 nucleotide substitutions, respectively. The novel species differed physiologically from R. sphaerocarpum in its abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…Other genes assembled were likewise genes expected to be present at high levels, such as R. glutinis 18S rRNA (HQ420261.1), R. mucilaginosa 18S rRNA (X84326.1) and R. taiwanensis RS1 complete mitochondrial genome (HF558455.1) as identified by best hit in the nt database. R. taiwanensis is a recently identified, novel Rhodotorula species closely related to R. mucilaginosa and R. glutinis var dairenensis whose entire mitochondrial genome was recently sequenced (Huang et al 2011) (Zhao et al 2013). It is one of the few Rhodotorula mitochondrial genomes in the database and likely indicative R. glutinis mitochondrial sequences, which are absent from the database.…”
Section: Resultsmentioning
confidence: 99%
“…Other genes assembled were likewise genes expected to be present at high levels, such as R. glutinis 18S rRNA (HQ420261.1), R. mucilaginosa 18S rRNA (X84326.1) and R. taiwanensis RS1 complete mitochondrial genome (HF558455.1) as identified by best hit in the nt database. R. taiwanensis is a recently identified, novel Rhodotorula species closely related to R. mucilaginosa and R. glutinis var dairenensis whose entire mitochondrial genome was recently sequenced (Huang et al 2011) (Zhao et al 2013). It is one of the few Rhodotorula mitochondrial genomes in the database and likely indicative R. glutinis mitochondrial sequences, which are absent from the database.…”
Section: Resultsmentioning
confidence: 99%
“…Cryp. taiwanensis pro tem was recently proposed based on one stain isolated from the surface of an unknown fern (Huang et al 2011). Half of the known strains of D. fabryi were reportedly isolated from skin infections, whereas other strains originated from sake and rice vinegar fermentation (Suzuki et al 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty strains were identified as belonging to five species in five genera of the phylum Basidiomycota. These five species were Rhodotorula mucilaginosa (14 strains), which was recently placed in the family Sporidiobolaceae, order Sporidiobolales, class Microbotryomycetes, and subphylum Pucciniomycotina ; Cutaneotrichosporon mucoides, which h a s b e e n t r a n s f e r r e d f r o m Tr i c h o s p o r o n t o Cutaneotrichosporon, and assigned to the family Trichosporonaceae, order Trichosporonales, class Tremellomycetes, and subphylum Agaricomycotina ; Cryptococcus taiwanensis pro tem, which was proposed as a novel species by Huang et al (2011); and Papiliotrema flavescens and Papiliotrema laurentii, which were recently transferred from the genus Cryptococcus to Papiliotrema in the family Rhynchogastremaceae, order Tremellales, class Tremellomycetes, and subphylum Agaricomycotina . Four strains were closest to the type strain of P. flavescens but differed by two nucleotide substitutions out of 559 nucleotides in the D1/D2 region of the LSU rRNA gene and nine nucleotide substitutions out of 451 nucleotides in the ITS region (Table 3, Fig.…”
Section: Yeast Isolation and Identificationmentioning
confidence: 99%
“…RS1 is closely related to Rhodotorula taiwanensis BCRC 23118 T , which was identified as a novel Rhodotorula species by Huang et al. (). Further comparison of the nuclear rRNA sequence showed that Rhodotorula sp.…”
Section: Resultsmentioning
confidence: 97%
“…; Choudhary and Johri ; Huang et al. ). Phylogenetic analysis of the D1/D2 domain or ITS region of the type strains of Rhodotorula and Rhodotorula sp.…”
Section: Resultsmentioning
confidence: 99%